Genome-wide association studies revealed genomic regions associated with production and reproduction traits in indicine cattle - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Tarannum Jahan (The Nucleus, 2026)

Emission of airborne nanoparticles from electric motors of household appliances - Yevgen Nazarenko; Elliot Zolfaghar; Devendra Pal; Léa Quellard; Parisa A. Ariya (Air Quality, Atmosphere & Health, 2025)
Nanoparticulate (ultrafine particle) indoor air pollution is an emerging concern. Evidence points to airborne nanoparticles’ potential adverse effects, including the impact on blood pressure, the pulmonary and cardiovascular systems, cognitive performance, oxidative stress, allergen sensitization, and inflammation. Nanoparticles originate from various sources. However, no study to date investigated emissions of nanoparticles and fine particles from electric motors in household appliances, ubiquitous indoors. This study fills this knowledge gap with an investigation of incidental emission of aerosol particles from seven electric motors taken from household appliances. The appliances were made by several different manufacturers and tested at the respective appliance’s maximum and minimum power settings as intended for use by the consumer. Aerosols were continuously measured and characterized during 24-hour measurement periods using a NanoScan scanning mobility particle sizer (SMPS). Two of the seven motors (AP B and AP G) emitted very few particles, with an average total number concentration below 10 cm − 3 . One electric motor (AP E) emitted over 170 times more aerosol particles at the maximum power setting compared to the minimum power setting. Another motor (AP A) had the highest emission of all motors at both the minimum and the maximum power settings. The total number concentration of aerosol particles exceeded 2700 cm − 3 and 3900 cm − 3 when operating two of the investigated electric motors (AP A and AP E, respectively) at the maximum power setting. We recommend that manufacturers of electric motors and household appliances test fine and ultrafine aerosol particle emissions from their products and address the problem. The design of household appliances equipped with electric motors should consider low-aerosol-emission motors and/or the installation of high-efficiency air filters in the motor air cooling duct(s) downstream of the electric motors.

Influence of pruning intensity on growth, yield and bio-chemical parameters of guava (Psidium guajava L.) Cv. Shweta under North Indian conditions - Vibhu Pandey; Arvind Kumar; Khushboo Sharma; Deepesh Keshari; Amit Kumar; Devendra Pal (Vegetos, 2025)

Genome-wide association studies of milk composition traits in indicine Badri cattle using ddRAD sequencing approach - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Aashaq Hussain Dar; Oshin Togla (Tropical Animal Health and Production, 2025)

Effect of various chemical solutions on micropropagation efficiency, antioxidant activities and clonal fidelity analysis of in vitro developed plantlets in pomegranate (Punica granatum L.) using SSR markers - Devendra Pal; Mukesh Kumar; Manoj Kumar Yadav; Chetan Chauhan; Arvind Kumar; Ujjwal Sirohi; V. Rakesh Sharma; Veena Chaudhary (Vegetos, 2024)

Genome-wide identification and annotation of SNPs and their mapping in candidate genes related to milk production and fertility traits in Badri cattle - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Manish Kumar Verma; Abhishek Pathak; Aashaq Hussain Dar; Anil Kumar; Rabendra Kumar Sharma (Tropical Animal Health and Production, 2023)

PM2.5 decadal data in cold vs. mild climate airports: COVID-19 era and a call for sustainable air quality policy - Rodrigo Rangel-Alvarado; Devendra Pal; Parisa Ariya (Environmental Science and Pollution Research, 2022)

Plant growth promoting Bacillus-based bio formulations improve wheat rhizosphere biological activity, nutrient uptake and growth of the plant - Priyanka Chandra; Rinki Khobra; Parul Sundha; Rakesh Kumar Sharma; Poonam Jasrotia; Amaresh Chandra; Devendra Pal Singh; Gyanendra Pratap Singh (Acta Physiologiae Plantarum, 2021)

Ameliorative role of bosentan, an endothelin receptor antagonist, against sodium arsenite–induced renal dysfunction in rats - Ashwani Kumar Sharma; Japneet Kaur; Tajpreet Kaur; Balbir Singh; Harlokesh Narayan Yadav; Devendra Pathak; Amrit Pal Singh (Environmental Science and Pollution Research, 2021)

Estradiol attenuates ischemia reperfusion-induced acute kidney injury through PPAR-γ stimulated eNOS activation in rats - Amrit Pal Singh; Nirmal Singh; Devendra Pathak; Preet Mohinder Singh Bedi (Molecular and Cellular Biochemistry, 2019)

Impact of tropical convection and ENSO variability in vertical distributions of CO and O3 over an urban site of India - L. K. Sahu; Varun Sheel; M. Kajino; M. Deushi; Sachin S. Gunthe; P. R. Sinha; Ravi Yadav; Devendra Pal; P. Nedelec; Valérie Thouret; Herman G. Smit (Climate Dynamics, 2017)

Dipyridamole attenuates ischemia reperfusion induced acute kidney injury through adenosinergic A1 and A2A receptor agonism in rats - Nikkita Puri; Vinita Mohey; Manjinder Singh; Tajpreet Kaur; Devendra Pathak; Harpal Singh Buttar; Amrit Pal Singh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)